Exchange Rate Depreciation, Wage Resistance and Inflation in Argentina (1882–2009). (16th July 2017) - Vernengo, Matias; Perry, Nathan
Abstract : This paper describes some of the main alternatives to the dominant neoclassical theories of inflation, according to which inflation is always a monetary phenomenon. The model develops a cost‐push approach, in which rising costs are mainly related to external constraints. Not only is inflation seen as resulting from balance of payments crises, but fiscal crises also are the result of the initial balance of payments crises within this framework. Fiscal deficits, and all other excess demand pressures, are absent, so that high levels of inflation are compatible with an economy that is below full employment, and stabilization is independent of fiscal adjustments. The model is then tested using a Vector Autoregression model and finds strong evidence for alternative theories of inflation over the monetarist theory. The empirical section tests both the long period (1882–2009) and the modern period (1990–2007) analyzing the impact of wages, the nominal exchange rate, the output gap and the monetary base on inflation. The results show that the exchange rate (external constraints) has been the primary cause of inflation. Wages are a causal factor in both models, and the monetary base and output gap show low causality in the long period, and ambiguous results for the modern period.